Visual guide to neonatal cardiology - Alboliras, Ernerio T.; Hijazi, Ziyad M.; Lopez, Cecilio; Hagler, Donald J. (Hoboken, NJ : Wiley Blackwell, 2018)
'The Visual Guide to Neonatal Cardiology is a comprehensive, highly illustrated, reference covering the evaluation, diagnosis and management of cardiac disease in the newborn. Contains over 900 color illustrations, including patient photographs, chest roentgenograms, electrocardiograms, echocardiograms, angiocardiograms, 3D computed tomogramphy, magnetic resonance imaging, pathologic specimens, and other relevant visual aids Discusses the natural history of fetal heart disease and the rationale, indications, technique, and impact of fetal cardiac intervention Reviews the anatomy and physiology of the neonatal cardiovascular system, including differences within the fetal, transitional, neonatal, child and adult circulatory system Highlights key steps for taking a patient history, including detailed discussion of the cardiac examination (inspection, palpation and auscultation of heart sounds and murmurs) Presents over 35 morphologic conditions with sections covering introduction, epidemiology, etiology with accepted or postulated embryogenesis, pathophysiology, clinical presentation, physical examination findings, diagnostic evaluation, management, and prognosis Includes a neonatal formulary reviewing selected medications currently used for treatment of perioperative low cardiac output, congestive heart failure, pulmonary hypertension, sedation, pain and anticoagulation in neonates'--Provided by publisher.
Parasternal ViewSuprasternal View; References; Chapter 14 Cardiac Catheterization and Angiocardiography; Patent Ductus Arteriosus (Figures 14.1 and 14.2); Pulmonary Valve Stenosis (Figure 14.3); Critical Aortic Valve Stenosis (Figure 14.4); Coarctation of the Aorta (Figure 14.5); Major Aorto-Pulmonary Collateral Arteries (Figure 14.6); Transposition of the Great Arteries (Figure 14.7); Hypoplastic Left Ventricle (Figure 14.8); Total Anomalous Pulmonary Venous Connection (Figure 14.9); Rotational Angiography (Figure 14.10); References; Chapter 15 Computed Tomography.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 08, 2018).
Keywords: Heart -- Diseases; Newborn infants -- Diseases; Heart Diseases; Infant, Newborn, Diseases; Fetal Diseases; Infant, Newborn; Electronic books